(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It offers little in the way ofdefining classes of input which we believe to have similar error- detectingability. In fact, the valid input space on its own is suitable only forderiving a suite of random tests, each a member of the valid input space.Nevertheless, the valid input space is a useful template to define and has animportant role to play in the framework. As mentioned at the end of chapter 3,the valid input space of an operation must be the source of allspecification-based tests for the operation. This means that any test is anelement of the valid input space. It also means that any test template must bea subset of the valid input space. So, we can define a Z type for testtemplates for a certain operation, Op: TT Op == p VIS Op Note the subscripted use of theoperation name. This is a practice we will adopt for the remainder of thethesis. This definition defines TT Op to be the type of all test templates forOp. Schemas vs sets: The significanceof bindings It has already been noted that templates describe sets of test dataand that Z schemas are used to define templates. It may seem strange not to usesets to define templates. As mentioned in section 4.1, defining test data foran operation involves assigning values to the input components (both state andparameter) of the operation, that is, defining a binding between inputcomponent identifiers and values. Thus, a template intuitively defines a set ofbindings, which is exactly what a Z schema defines.